Who Owns War? (Leiden University Press, 2026)
This book provides a critical assessment of the broadly held view that states ‘own’ war. The central theme of the book is that the persistence of non-state actors in historical as well as contemporary conflicts challenges this narrative. It takes a multidisciplinary approach to address a host of questions concerning the role of non-state actors, both armed and unarmed, in conflict and their relationship with states. Recurring themes are issues of loyalty, accountability and effectiveness. Part I is subdivided into two separate themes. The first is the use of civilians in war from a legal and military operational perspective, the second the question of loyalty and accountability of the private sector. Part II considers the cases of several non-state armed actors from the past and the present, showcasing the variety of actors and roles they play. Together, the contributions to this book provide an important new perspective on the role of non-state (armed) actors in war.